Heterogeneous Loans and the Effect of Monetary Interventions - Gianluca Cafiso; Giulia Rivolta (Center for Economic Studies and ifo Institute (CESifo), 2021)
The amount of credit in the economy is a heterogeneous aggregate that can be analyzed across different dimensions. Considering such dimensions provides insights into the effect of monetary policy interventions because the credit components are observed to respond differently. Several possible motivations are behind such a differential response and those relate to either demand and supply factors intrinsic to the transmission mechanism of monetary policy. Our objective is to unveil such a differential response across a couple of relevant dimensions and discuss the possible causes behind what observed. The analysis refers to the US and is based on a vector auto-regression estimated using Bayesian techniques and identified with a combination of sign and zero-restrictions.
Keywords: E44; E51; G20; G21; C11; 330; bank loans; non-bank loans; monetary interventions; households; corporate business; non-corporate business; Bayesian VAR